EVALUATING THE EFFICIENCY OF MECHANISMS FOR FRAME BLOCKS TRANSMISSION IN NOISY CHANNELS OF IEEE 802.11 NETWORKS - Khandetskyi, V. S.; Karpenko, N. V.; Gerasimov, V.V. (Radio Electronics, Computer Science, Control, 2025)
Context. Aggregating frames into blocks when transmitting information in wireless IEEE802.11 networks helps to significantly reduce overhead costs and increase the transmission rate. However, the impact of noise reduces the efficiency of such transmission due to an increased probability of distortion of longer messages. We compared the efficiency of data transmission by variable and constant size blocks formed from frames using VBS and FBS mechanisms correspondingly under conditions of noise varying intensity. Objective. The purpose of this article is a comparative study of VBS and FBS mechanisms used for the formation and transmission of different sizes frame blocks under medium and high noise intensity. Method. A simple model used in IEEE 802.11 networks to determine the DSF throughput for transmitting frames in infrastructure domains was modified by us to transmit frame blocks of different sizes under conditions of medium and high intensity noise affecting the transmission process. We use for transmission a discrete in time Gaussian channel without memory. In such a channel, bit errors are independent and equally distributed over the bits of the frame. The scale factors of the model for the number of frames in a block k = 6–40 at an average noise level corresponding to BER = 10–6 and k = 4–15 for high-intensity noise at BER = 10–5 are determined. The algorithm for calculation of the network throughput has been generalized. The investigation of the dependences of the throughput on the number of frames in the VBS blocks showed the presence of local maxima in dependences, located in the region of average values of the frames number. These maxima are more pronounced at increased data transfer rates. Results. It is shown that with a small number of frames in a block (k = 6–9) and high-intensity noise, the efficiency of the FBS mechanism exceeds the efficiency of the VBS block formation mechanism. However, at the same noise level, an increase in the number of frames in a block (k ≥ 10) makes the use of the VBS mechanism more preferable. This advantage is explained by the fact that the VBS mechanism at each subsequent stage of transmission forms a block from frames distorted at the previous stage, therefore the size of the blocks at subsequent stages decreases, increasing the number of frames successfully transmitted to the AP (due to the increase in the probability of transmitting shorter blocks). At the same time, the constant and small probability of successful transmission of a constant size block at each stage makes the probability of transmission of frames distorted at the previous stages low. The situation changes for noise of medium intensity. Here the transmission of each subsequent block in the range of up to 25 frames per block using the VBS method requires the use of two stages. The application of the FBS method in these conditions shows that only the first set of frames requires the use of two stages for its complete transmission. Then, due to the accumulation of frames at the previous stages, each subsequent stage of transmission completes the formation of the corresponding set in the memory of AP. Thus, when the noise intensity decreases to BER = 10–6 and below, the use of the FBS mechanism becomes more effective. The obtained results are illustrated with specific examples characterizing the formation and transmission of various frame blocks. Conclusions. In this article, using a mathematical model modified by us, a comparative study was conducted on the efficiency of various mechanisms for forming and transmitting a frame block of different sizes under conditions of the impact of different intensity noise on the transmission process. The algorithm for calculating the network throughput was generalized, and the values of the throughput were determined when using the VBS and FBS network functioning mechanisms.